2017
DOI: 10.1159/000484552
|View full text |Cite
|
Sign up to set email alerts
|

Synchronous Primary Renal Cell Carcinoma and Pancreatic Ductal Adenocarcinoma: Case Report and Literature Review

Abstract: Synchronous primary cancers involving the pancreas and kidney are extremely rare and poorly documented. We report the first case of this association treated with chemotherapy and tyrosine kinase inhibitor. A 70-year-old woman presented with a 2-month history of epigastric pain with weight loss of 12 kg. Two weeks previously, she had presented with jaundice and pelvic pain. A computed tomography (CT) scan of the body revealed the presence of an irregular mass in the body of the pancreas, encasing the celiac tru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 7 publications
0
7
0
Order By: Relevance
“…40,41 In 2-4% multiple primary tumors can occur in other organs at time of initial RCC presentation, but two independent primary tumors of the kidney and pancreas are extremely rare. 31 According to our review, the first reported case of second/double primary cancer involving the pancreas and the kidney was published in 1969. 42 Since then, to the best of our knowledge, there have been fewer than 25 of such cases reported in the literature with two independent primaries of RCC and pancreatic tumors, synchronous metastasis of RCC to the pancreas, pancreatic cancer with metastases to the kidney, and RCC with benign solid pancreatic lesions.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…40,41 In 2-4% multiple primary tumors can occur in other organs at time of initial RCC presentation, but two independent primary tumors of the kidney and pancreas are extremely rare. 31 According to our review, the first reported case of second/double primary cancer involving the pancreas and the kidney was published in 1969. 42 Since then, to the best of our knowledge, there have been fewer than 25 of such cases reported in the literature with two independent primaries of RCC and pancreatic tumors, synchronous metastasis of RCC to the pancreas, pancreatic cancer with metastases to the kidney, and RCC with benign solid pancreatic lesions.…”
Section: Discussionmentioning
confidence: 93%
“…Likewise, no specific form of adjuvant chemotherapy, tyrosine kinase inhibitors, RANK ligand inhibitors, immunotherapy, nor radiation has evolved over the years. 30,31,33 The literature is unclear in recommending specific therapeutic agents in these patients. Although these aforementioned adjuvant agents are extensively reported in the literature for use in pancreatic cancer and RCC, 44,45 the extremely low number of patients presenting with synchronous tumors in kidney and pancreas does not allow any kind of prospective and randomized clinical trials.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to this, a team of surgeons also shared their experience of laparoscopic removal of RCC and sigmoid colon cancer simultaneously [9-11]. Another case report has also highlighted the management of concurrent RCC and pancreatic ductal adenocarcinoma [12, 13].…”
Section: Discussionmentioning
confidence: 99%
“…Nowadays, there are just a few reports of aDTC in the context of MPMN 50–54 and there is no definitive published clinical evidence supporting the use of MKIs in patients with MPMNs and aDTC. The usefulness of MKIs in patients with MPMNs (including DTC) has been described in some patients though, with comparable results to those in a non‐MPMN context 53,55–58 . Despite the lack of sound clinical evidence, there is sufficient pathophysiological rationale to use MKIs, particularly lenvatinib alone or in combination, for specific combinations of MPMNs, including DTC and most common associated SPCs 48,49,59 .…”
Section: Treatment Recommendationsmentioning
confidence: 99%
“…The usefulness of MKIs in patients with MPMNs (including DTC) has been described in some patients though, with comparable results to those in a non‐MPMN context. 53 , 55 , 56 , 57 , 58 Despite the lack of sound clinical evidence, there is sufficient pathophysiological rationale to use MKIs, particularly lenvatinib alone or in combination, for specific combinations of MPMNs, including DTC and most common associated SPCs. 48 , 49 , 59 Furthermore, there might be an even greater potential benefit of combining an MKI and a TKI for treatment of advanced malignancies (including DTC) according to therapeutic molecular targets based on common driver gene alterations and/or activated (initial or escape) signaling pathways.…”
Section: Treatment Recommendationsmentioning
confidence: 99%